Training degree assessment of staff producing parenteral nutrition in Pharmacy Services - Rosa Mª Romero Jiménez; Pilar Gomis Muñoz; Cristina Crespo; Guadalupe Piñeiro; Juan Carlos Pérez-Pons; Sonsoles García Rodicio; Carmen Ripa Ciaurriz; Vicente Gimeno Ballester; Cristina Vázquez; Mercedes Cervera; Mª Victoria Calvo; Pilar Tejada (Elsevier, 2016)
Objective: To assess the level of expertise of Pharmacy personnel in the manufacturing of total parenteral nutrition. Material and methods: An on-line survey including 17 questions concerning key aspects of TPN manufacturing was designed. Survey monkey software was used to create the survey and to analize its results. Results: 135 answers were received. 95% of the participant Pharmacy services had written standard manufacturing procedures. 67% answered that phosphate salts should be the first electrolite to be additioned into the total parenteral nutrition and 34% affirmed that validation of the aseptic manufacturing technique was not performed. As far as personnel training was concerned, 19% of respondents had not received any specific training, although 99% considered it would be necessary to receive it. Conclusions: The polled personell has an acceptable level of expertise but adequate training courses are still necessary and should be promoted from Pharmacy services